Age and Cancer Incidence in 5.2 Million People With Human Immunodeficiency Virus (HIV): The South African HIV Cancer Match Study. (3rd December 2022) - Ruffieux, Yann; Muchengeti, Mazvita; Olago, Victor; Dhokotera, Tafadzwa; Bohlius, Julia; Egger, Matthias; Rohner, Eliane
Abstract: Background: Old age is an important risk factor for developing cancer, but few data exist on this association in people with human immunodeficiency virus (HIV, PWH) in sub-Saharan Africa. Methods: The South African HIV Cancer Match study is a nationwide cohort of PWH based on a linkage between HIV-related laboratory records from the National Health Laboratory Service and cancer diagnoses from the National Cancer Registry for 2004–2014. We included PWH who had HIV-related tests on separate days. Using natural splines, we modeled cancer incidence rates as a function of age. Results: We included 5 222 827 PWH with 29 580 incident cancer diagnoses—most commonly cervical cancer (n = 7418), Kaposi sarcoma (n = 6380), and breast cancer (n = 2748). In young PWH, the incidence rates for infection-related cancers were substantially higher than for infection-unrelated cancers. At age 40 years, the most frequent cancer was cervical cancer in female and Kaposi sarcoma in male PWH. Thereafter, the rates of infection-unrelated cancers increased steeply, particularly among male PWH, where prostate cancer became the most frequent cancer type at older age. Whereas Kaposi sarcoma rates peaked at 34 years (101/100 000 person-years) in male PWH, cervical cancer remained the most frequent cancer among older female PWH. Conclusions: Infection-related cancers are common in PWH in South Africa, but rates of infection-unrelated cancers overtook those of infection-related cancers after age 54 years in the overall study population. As PWH in South Africa live longer, prevention and early detection of infection-unrelated cancers becomes increasingly important. Meanwhile, control strategies for infection-related cancers, especially cervical cancer, remain essential. Abstract : We studied the association between age and the incidence of various cancers in people living with the human immunodeficiency virus in South Africa. The risk of most, but not all, cancer types increased with age.